The Influence of Service Quality Dimensions towards Customer Satisfaction and Customer Loyalty - Ramadhani, Rizky; Raafaldini Mirzanti, Isti (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. Coffee consumption in Indonesia has been increasing in the past few years, thus promoting new coffee shops to open each year. The key factors in building a successful coffee shop is through the continuous improvement of the product and its service. Good product in coffee industry can be defined as a good taste and aroma coffee, from its acidity and its sweetness. Through service, a coffee shop could gain loyal customers whenever they are satisfied and will return as repetitive customers, thus creating a sustainable coffee shop. This research aims to find out service quality, customer satisfaction, and customer loyalty of Jack Runner Roastery. This research is using a quantitative approach by distributing questionnaires to Jack Runner Roastery’s customer. The correlation between service quality dimensions and customer satisfaction is analyzed using multiple linear regression, while customer satisfaction towards customer loyalty is analyzed using simple linear regression. Results shows that reliability, tangibles, empathy and responsiveness have a positive significant influence towards customer satisfaction, while assurance has no significant influence. Furthermore, the study shows that customer satisfaction has a significant influence towards customer loyalty. The research provides recommendation for coffee shops to improve their service quality to gain customer satisfaction and customer loyalty. Keywords: Customer Loyalty, Customer Satisfaction, Service Quality.